PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL PEMODERASI (STUDI KASUS PADA KONSUMEN GOJEK DI KOTA BANJARMASIN) - Boy Sapto Suryo Subiantoro (At-Tadbir : jurnal ilmiah manajemen, 2020)
The presence of transportation services in the network is currently a separate phenomenon in the community. Where many services are provided in order to facilitate consumers both in terms of transportation and other services. And to find out the relationship between service quality and consumer loyalty, both directly and through customer satisfaction variables in consumers of transportation companies in the network, namely Gojek in Banjarmasin, the research was conducted using data collection media, namely questionnaires. Testing data using multiple linear regression analysis, as well as through the test results of the multak difference. Based on multiple linear regression testing conducted, it is known that both together and partially service quality variables and customer satisfaction can affect customer loyalty with a significant value obtained below the level of significant 5%. While testing the relationship of service quality to customer loyalty through customer satisfaction by performing the absolute difference test results in a significant value of 0.157 or more than the level of significant 0.05 so that the results are declared no influence.Keywords: Quality of Service, Consumer Satisfactions, Consumer Loyalty, Online Transportation Service